Memory of cell shape biases stochastic fate decision-making despite mitotic rounding - Takashi Akanuma (Nature Portfolio, 2016)
Cell shape influences function but during mitotic cell rounding the original shape is lost. Here the authors show that the cellular eccentricity of progenitor cell biases stochastic fate-decisions using a combination of quantitative live imaging, genetic manipulations and computational simulations.